2017
DOI: 10.17221/9/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity and population structure of five Chinese indigenous donkey breeds using microsatellite markers

et al.

Abstract: China had the largest population of raising donkeys in the world, however the number of Chinese indigenous donkey decreased dramatically due to the increase of agriculture mechanization in the last century. The species has still been important in China because of its edible and medical value, therefore the survey on its genetic diversity in China is necessary for its conservation and utilization. In this study, 15 microsatellite markers were used to evaluate genetic diversity and population structure of five C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…These results are comparable to the previous values reported in Balkan donkeys [35], Spanish donkeys [36] and Catalonian donkeys [37]. In terms of mean number of alleles, the genetic variability observed in the 16 Turkish donkey populations was lower than that reported in Catalonian donkey breed [37], five Spanish breeds [36], three Croatian donkey populations [38], 15 indigenous Chinese donkey breeds [39][40][41][42], Balkan donkeys [35] and Tunisian donkeys [43], but higher than that observed in the seven indigenous Italian donkey breeds [44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are comparable to the previous values reported in Balkan donkeys [35], Spanish donkeys [36] and Catalonian donkeys [37]. In terms of mean number of alleles, the genetic variability observed in the 16 Turkish donkey populations was lower than that reported in Catalonian donkey breed [37], five Spanish breeds [36], three Croatian donkey populations [38], 15 indigenous Chinese donkey breeds [39][40][41][42], Balkan donkeys [35] and Tunisian donkeys [43], but higher than that observed in the seven indigenous Italian donkey breeds [44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
“…The results of microsatellite polymorphism revealed relatively high degree of heterozygosity in the Turkish donkey populations investigated in this study. Among Turkish donkey populations, the H E ranged from 0.6294 (ISP) to 0.6983 (ANT), which showed a comparable level to the previous values reported in Spanish donkeys [ 36 ], Catalonian donkey breeds [ 37 ], Croatian coast donkey populations [ 48 ], Balkan donkey breeds [ 35 ], Tunisian donkeys [ 43 ], Chinese donkey breeds [ 39 , 40 , 41 , 42 ] and was more diversified than Italian [ 44 , 45 , 46 , 47 ] and American donkeys [ 49 ]. This finding indicates that there are appreciable differences in the level of genetic variability among 16 Turkish donkey populations.…”
Section: Discussionsupporting
confidence: 81%
“…These results indicate that there are no appreciable differences in the level of genetic variability among the Croatian donkey breeds. Istrian donkey and Littoral-Dinaric donkey populations have a lower average number of alleles compared to five native Spanish breeds (range from 7.0 to 7.5) [14], four Chinese breeds (range from 6.0 to 6.80) [58], or donkey breeds from the Balkans (9.3) [19], but they are higher than two Sicilian native breeds (4.05) [59]. Comparing observed and expected heterozygosity, the values of Istrian donkey and Littoral-Dinaric donkey populations are mostly between the reported values of previous studies [20,58], with averages of H O = 0.560 and H E = 0.70, and H O = 0.63-0.71, H E = 0.93-0.70.…”
Section: Discussionmentioning
confidence: 94%
“…The results indicated that the microsatellites of similar species are conserved and could be used to analyze the genetic diversity of donkeys. Researchers also needed to have a deeper understanding of the genetic information and genetic relationships within and among breeds to obtain more accurate and generalized conclusions, which could be more effectively applied to the conservation and further utilization of donkey breeds [ 35 , 36 , 37 ]. In terms of average allele number, the genetic variability observed in three Sicilian donkey breeds should be lower than in five Spanish and three Croatian breeds but higher than in the Italian Amiata donkey [ 38 ].…”
Section: Research On Genetic Materialsmentioning
confidence: 99%